PENGARUH PROFITABILITAS, LEVERAGE, STRUKTUR MODAL, DAN KEBIJAKAN DIVIDEN TERHADAP NILAI PERUSAHAAN - Meylani Dwi Anggorowati; Meifida Ilyas (Pasca Sarjana Universitas Satya Negara Indonesia, 2022)
The purpose of this study was to determine the effect of Profitability, Leverage, Capital Structure and Dividend Policy on Firm Value in food and beverage companies on the Indonesia Stock Exchange (IDX) for the period 2015 – 2019. The total population of companies during the study period was 25, which met the criteria for the sample that had been carried out only 6 companies. The sample was carried out by purposive sampling method. The research design used is causal research. The type that is secondary data or indirect data and data analysis using multiple regression analysis with SPSS version 22 system. The results partially show that profitability has a negative effect on firm value, leverage has a positive effect on firm value, capital structure has a negative effect on firm value, and dividend policy has no effect on firm value. Meanwhile, simultaneously, the research results show that Profitability, Leverage, Capital Structure and Dividend Policy simultaneously have a significant effect on firm value. Testing the coefficient of determination shows that Profitability, Leverage, Capital Structure and Dividend Policy affect 0.711 or 71.1% of firm value and the remaining 28.9% is explained by other variables not included in this research model.